Evolution of Multi-Entity Collaborative Innovation of Sports Industry Cluster Based on Complex Network - Shanshan Zhao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Under the influence of the dual-wheel driven mechanism of the economy, diverse market demand imposes greater demands on enterprises in the sports industry cluster, and the diffusion of production technology innovation in the sports industry cluster is developing and evolving towards multi-entity collaboration. However, few existing studies on the behavior and strategy of multi-entity collaborative innovation examine clusters in the sports industry. This study seeks to analyze the evolution of multi-entity collaborative innovation within a complex network-based sports industry cluster. Utilizing research methods such as questionnaire design, data collection, variable measurement, and structural equation modeling, this study employed SPSS and AMOS to perform data analysis and model analysis, and empirically validated the theoretical model and research assumptions. Last but not least, the corresponding experimental results were presented, which demonstrated the efficacy of the proposed analysis method and the fact that innovation investment intensity has a positive influence on maximum enterprise benefit and cluster sales.